THE ROLE OF INNOVATIVE INFRASTRUCTURE IN ENHANCING ENTREPRENEURIAL EFFICIENCY (The Conference Hub, 2025)
This thesis examines the critical role of innovative infrastructure in enhancing entrepreneurial efficiency within modern economic systems. It highlights how elements such as technology parks, business incubators, digital platforms, and logistics networks contribute to reducing operational costs, accelerating innovation adoption, and increasing competitiveness among small and medium-sized enterprises. The study emphasizes that well-developed innovative infrastructure not only supports the commercialization of new ideas but also fosters an ecosystem that enables sustainable entrepreneurial growth. The research results show that integrating innovation-driven infrastructure significantly improves productivity, resource utilization, and the overall effectiveness of entrepreneurial activities.